A 0.079 mm2 2.1-to-4.2 GHz ring-VCO employing programmable current topology - Awais, Muhammad; Ramiah, Harikrishnan; Lim, Chee Cheow; Chuah, Joon Huang (Emerald, 2018)
Purpose: The purpose of this work in designing a wideband ring voltage-controlled oscillator (VCO) based on programmable current topology. It occupies a very tiny area yet achieving a good phase noise performance, which is suitable to be implemented in cost-effective and wideband frequency synthesizers. Design/methodology/approach: The tuning range and gain are improved by dividing the VCO tuning curve into multiple curves controlled by programmable current sources without introducing additional parasitic capacitance. Findings: Fabricated in 130-nm standard complementary metal oxide semiconductor technology and occupying an area of 0.079 mm2, the VCO is tunable from 2.05 to 4.19 GHz, with a tuning percentage of 68.5 per cent. The VCO measures a phase noise performance of −96.7 dBc/Hz at an offset of 1 MHz from a 4.19 GHz carrier while consuming an average current of 6.5 mA, achieving figure of merit (FoM) and FoMT of −158.9 and −175.6 dBc/Hz, respectively. Originality/value: The proposed design uses programmable current topology without introducing parasitic capacitance, hence achieving wideband operation. It also occupies a tiny area and achieves a good phase noise performance.